Peripheral Mechanisms Underlying Bacillus Calmette–Guerin-Induced Lower Urinary Tract Symptoms (LUTS) - Meera Elmasri; Aaron Clark; Luke Grundy (Brain Sciences)
Non-muscle invasive bladder cancer (NMIBC) accounts for approximately 70–75% of all bladder cancer cases. The standard treatment for high-risk NMIBC involves transurethral tumour resection followed by intravesical Bacillus Calmette–Guerin (BCG) immunotherapy. While BCG immunotherapy is both safe and effective, it frequently leads to the development of lower urinary tract symptoms (LUTS) such as urinary urgency, frequency, dysuria, and pelvic discomfort. These symptoms can significantly diminish patients’ quality of life and may result in the discontinuation of BCG treatment, adversely affecting oncological outcomes. Despite the considerable clinical impact of BCG-induced LUTS, the underlying mechanisms remain unclear, hindering the implementation or development of effective treatments. This review provides novel insights into the potential mechanisms underlying BCG-induced LUTS, focusing on the integrated roles of afferent and efferent nerves in both normal and pathological bladder sensation and function. Specifically, this review examines how the body’s response to BCG—through the development of inflammation, increased urothelial permeability, and altered urothelial signalling—might contribute to LUTS development. Drawing from known mechanisms in other common urological disorders and data from successful clinical trials involving NMIBC patients, this review summarises evidence supporting the likely changes in both sensory nerve signalling and bladder muscle function in the development of BCG-induced LUTS. However, further research is required to understand the intricate mechanisms underlying the development of BCG-induced LUTS and identify why some patients are more likely to experience BCG intolerance. Addressing these knowledge gaps could have profound implications for patients’ quality of life, treatment adherence, and overall outcomes in NMIBC care.